Edukasi dan Implementasi Aromaterapi Lavender Sebagai Upaya Relaksasi pada Ibu Hamil Trimester Ketiga di Kelurahan Cipageran : Penelitian - Hidayat, Monna Maharani; Imelisa, Rahmi; Wisnusakti, Khrisna (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The third trimester of pregnancy is often associated with increased physical and psychological discomforts, including anxiety, sleep disturbances, and emotional tension, which may affect maternal and fetal well-being. Safe and easily applicable non-pharmacological interventions are needed to promote relaxation among pregnant women. Lavender aromatherapy is known for its calming effects and potential to reduce anxiety. This community service program aimed to provide education and implement lavender aromatherapy as a relaxation strategy for third-trimester pregnant women in Cipageran Village. The methods included health education, demonstration of lavender aromatherapy use, and direct practice assistance. Evaluation was conducted by assessing relaxation levels and subjective complaints before and after the intervention. The results indicated increased relaxation, reduced anxiety complaints, and improved rest quality among pregnant women following the implementation of lavender aromatherapy. The program also enhanced participants’ knowledge and skills in utilizing complementary therapy independently. In conclusion, education and implementation of lavender aromatherapy represent a safe, practical, and supportive intervention to improve comfort and well-being among third-trimester pregnant women at the community level.